Lefal Aspects of Labor Migration and Human Trafficking - Kukhianidze, Lasha (European Scientific Journal, ESJ, 2017)
The paper deals with the legal aspects of the problems of labor migration and human trafficking, its causes and factors, the trafficking scale. When considering economic causes, we refer to the demand for low-cost labor, as a characteristic factor of globalization which, in turn, greatly effects the international labor migration and is one of the root causes of human trafficking. In the analysis of the social causes, the focus is mainly made on the low-pay employment or lack of working conditions.